Mammalian Inner Ear-Resident Immune Cells—A Scoping Review - Betül Karayay; Heidi Olze; Agnieszka J. Szczepek (Cells, 2024)
Background: Several studies have demonstrated the presence of resident immune cells in the healthy inner ear. Aim: This scoping review aimed to systematize this knowledge by collecting the data on resident immune cells in the inner ear of different species under steady-state conditions. Methods: The databases PubMed, MEDLINE (Ovid), CINAHL (EBSCO), and LIVIVO were used to identify articles. Systematic reviews, experimental studies, and clinical data in English and German were included without time limitations. Results: The search yielded 49 eligible articles published between 1979 and 2022. Resident immune cells, including macrophages, lymphocytes, leukocytes, and mast cells, have been observed in various mammalian inner ear structures under steady-state conditions. However, the physiological function of these cells in the healthy cochlea remains unclear, providing an opportunity for basic research in inner ear biology. Conclusions: This review highlights the need for further investigation into the role of these cells, which is crucial for advancing the development of therapeutic methods for treating inner ear disorders, potentially transforming the field of otolaryngology and immunology.